Earned Value (EV) Management Model for Small Software Development Projects - Ray, Jeffrey; Sanderson, Sandra (My University, 2001)
This paper describes an approach for implementing earned value (EV) management tracking on small software development projects. Small projects are difficult EV applications because work must be tracked down at the task level so it can be costed out and used as a basis for the budgeted and scheduled work plan. Small projects are very dynamic and establishing a baseline plan down to the task level can be futile when outside factors such as changing requirements, funding profiles, and staffing levels would require that the baseline plan be constantly updated and re-baselined. In some cases, such as a small software development effort, it is not worth the effort to plan the project down to the level of project control required to develop cost-loaded schedules of tasks. An EV approach is discussed below where percent complete credit for work performed is granted based on achieving key milestones, as opposed to a project manager’s assessment of how much each additional task has been completed. By eliminating the need to track progress down at the detailed task level this weighted milestone EV model recommended below can accommodate differences between how work is planned, and actually carried out, without requiring updating of the baseline plan. In retrospect, it makes sense to track progress according to the last milestone that has been achieved. After successfully completing a milestone, the first action project management takes is to start planning how to complete the deliverables for the next key milestone event. Since the work planning and execution revolves around achieving milestone events, they are the likely focus of any EV model that attempts to rise out of the specific details of preparing and maintaining resource and cost loaded schedules. This paper provides a description of such an EV model, one that tracks work progress according to milestones achieved, and also provides insight concerning how to implement the model.